The Effects of Family Status on Applicants' Hiring Likelihood in Iceland - Ásdís Svava Hallgrímsdóttir 1987- (2014)
Important qualities are evaluated when applicants are selected for a job. Despite that people who are excellently qualified are for some reason sometimes not recruited. Recent studies have demonstrated discrimination against women, when it comes to age and family status, as concerns getting a job. The main purpose of this study was to measure whether family status, age and gender affects the likelihood of getting a job, as well as the effects of these three qualities on the offered salary. It was hypothesized that women aged 37, with children are more likely hired than women aged 27, without children. Likewise, women aged 27, with children are more likely hired than women aged 37, with children. Also, no discrimination against men was to be found. A total of 456 participated and 153 of them had hiring or managerial experience. The study was an experimental survey design. None of the hypotheses were supported. Other results added support for the discrimination against younger women without children. Discrimination against older men and men with children was found, which has not been found before. Further research is needed on this subject. Þegar val stendur á milli starfsumsækjenda eru mikilvægir eiginleikar þeirra metnir. Það kemur þó fyrir að mjög hæfir einstaklingar eru ekki valdir til starfa af einhverjum ástæðum. Nýlegar rannsóknir hafa sýnt þá mismunun sem konur verða fyrir gagnvart aldri og fjölskylduhögum á líkur á að hljóta starf. Megintilgangur rannsóknarinnar var að athuga hvaða áhrif fjölskylduhagir, aldur og kyn hefðu á líkur á starfi, sem og, áhrif þessara þriggja þátta á hversu há laun umsækjendum var boðið. Tilgátur rannsóknarinnar voru: 37 ára konur með börn fá hærri líkur á starfi en 25 ára barnlausar konur, 27 ára konur með börn fá hærri líkur á starfi en 37 ára konur með börn og karlar verða ekki fyrir mismunun. Þátttakendur voru samtals 456, en af þeim voru 153 með stjórnunar- eða ráðningarreynslu og var rannsóknarsnið tilraunarinnar í formi spurningakönnunar. Tilgátur voru ekki studdar. ...